Immunization Program Intervention Training in Stunting Prevention Effort in Sampang Regency, Madura Island, East Java - Arief Hargono; Laura Navika Yamani; Farah Fadhilah; Taufiq Hidayat Hasan; Kurnia Dwi Artanti (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
Introduction: Stunting is still a major health problem in Indonesia. Sampang Regency was one of the districts that experienced an increase in the prevalence of stunting. According to the 2018 Riskesdas data, one in three babies under two years old (baduta) and babies under five years old (toddlers) in Indonesia are in the stunting category. The intervention was needed to increase the number of immunization to prevent stunting. This activity aimed to identify the barrier to increasing Universal Coverage Immunization (UCI) to solve the immunization problem using the Human Centered-Design (HCD) method. Methods: The method used is a qualitative method using HCD with in-depth interviews, which is a method used to explore problems from the community side. This activity was involved by the head of the epidemiology and immunization section, the program holders of the Sampang district health office, coordinating midwives and immunization coordinators at selected health centers regarding immunization program interventions, namely exploring immunization problems from the community. The number of informants were six people in every public health center. The HCD intervention method has several steps: Persona, Journey of Map, Quote, Findings and Suggestions. The data analysis technique used a description of every HCD step. Results: The results from the intervention were that every public health center is known to have a different picture related to portraits of community members who are influential in implementing the immunization program. Conclusions: This program showed that health was not only the responsibility of the government or the health program holders but everyone. The recommendations from the HCD training at the two public health centers agreed to re-advocate the immunization program to relevant stakeholders.